Correction: Feeding styles and adiposity in children of 6 months- 5 years of age: Protocol for a systematic review and meta- analysis. - Divya Nair Haridas; Onno C P van Schayck; Giridhar R Babu; N Sreekumaran Nair; Prafulla Shriyan (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0292139.].